Requirement of Adaptor Protein GULP during Stabilin-2-mediated Cell Corpse Engulfment - Seung-Yoon Park; Kae-Bok Kang; Narendra Thapa; Sang-Yeob Kim; Sung‐Jin Lee; In‐San Kim (2008)
The prompt clearance of cells undergoing apoptosis is critical during embryonic development and normal tissue turnover, as well as during inflammation and autoimmune responses. We recently demonstrated that stabilin-2 is a phosphatidylserine receptor that mediates the clearance of apoptotic cells, thereby releasing the anti-inflammatory cytokine, transforming growth factor-beta. However, the downstream signaling components of stabilin-2-mediated phagocytosis are not known. Here, we provide evidence that the adaptor protein, GULP, physically and functionally interacts with the stabilin-2 cytoplasmic tail. Using fluorescent resonance energy transfer analysis and biochemical approaches, we show that GULP directly binds to the cytoplasmic tail of stabilin-2. Knockdown of endogenous GULP expression significantly decreased stabilin-2-mediated phagocytosis. Conversely, overexpression of GULP caused an increase in aged cell engulfment. The phosphotyrosine binding (PTB) domain of GULP was sufficient for the interaction with stabilin-2; therefore, transduction of TAT fusion PTB domain acts as a dominant negative, resulting in impaired engulfment of aged red blood cells in stabilin-2 expressing cells. In addition, the PTB domain of GULP was able to specifically interact with the NPXY motif of the stabilin-2 cytoplasmic tail. Taken together, these results indicate that GULP is a likely downstream molecule in the stabilin-2-mediated signaling pathway and plays an important role in stabilin-2-mediated phagocytosis.